Space and Time: An Impact of Spatial Separation, Apparent Motion, and Perceptual Grouping on TOJ Performance. (May 2013) - Baruch, Orit; Yeshurun, Yaffa; Shore, David I
This study explored the effects of spacing and objecthood (ie grouping based on closure) on temporal order judgment (TOJ) with displays that either involved successive onset of the target stimuli, resulting in apparent motion (experiments 1 and 2), or included simultaneous onset but successive shortening of the stimuli, and therefore did not result in apparent motion (experiment 3). We found a robust effect of spatial separation whose nature depended on whether or not the display allowed the emergence of illusory motion. Specifically, with apparent motion TOJ was best with the smallest spacing, but without it TOJ was worst with the smallest spacing. Moreover, overall accuracy was better with, than without, apparent motion. A small effect of objecthood—poorer TOJ performance when the elements formed an object—emerged only when spacing was not manipulated. These findings suggest that different mechanisms mediate temporal processing when we have access to motion information than when we do not.